Polar Constituents and Biological Activity of the Berry-Like Fruits from Hypericum androsaemum L. - Caprioli, Giovanni; Alunno, Alessia; Beghelli, Daniela; Bianco, Armandodoriano; Bramucci, Massimo; Frezza, Claudio; Iannarelli, Romilde; Papa, Fabrizio; Quassinti, Luana; Sagratini, Gianni; Tirillini, Bruno; Venditti, Alessandro; et al. (Frontiers in Plant Science, 2016)
Hypericum androsaemum, also known as Tutsan, is a small evergreen shrub common in the Mediterranean basin where it is traditionally used as diuretic and hepatoprotective herbal drug. This plant possesses the peculiarity to produce fleshy and berry-like fruits that ripen from red to shiny black. In the present work, the chemical constituents of methanolic extracts and infusions of red and black fruits were analyzed by HPLC, and correlated with their antioxidant properties which were evaluated by the DPPH, β-Carotene/linoleic acid and hypochlorous acid tests. In addition, the red pigment of the fruit was isolated by column chromatography and structurally elucidated by NMR. Results showed that H. androsameum fruits contain high amounts of shikimic and chlorogenic acids, while their color was given by a tetraoxygenated-type xanthone, reported for the first time in Hypericum species. The red berries infusion gave the highest content of total phenolic compounds, DPPH and hypochlorous acid scavenging activity, and β-carotene bleaching. Cytotoxicity of the berries extracts on three human tumor cell lines (malignant melanoma, breast adenocarcinoma and colon carcinoma) was evaluated by MTT assay, and relevant inhibition on colon carcinoma cells (IC50 value of 8.4 µg/mL) was found. Finally, the effects of red berries extract on the immune system were evaluated by peripheral blood mononuclear cell (PBMC) proliferation assay that revealed a strong stimulation on lymphocytes at low doses (0.4-6 µg/mL).